Polysemantic Somatic Phrases in Uzbek and Their Stylistic Colors (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The phenomenon of polysemy present in linguistics is inherent in both speech and expression, but the degree of distribution of this phenomenon in vocabulary and phraseology is not the same.The article provides information on the phenomenon of ambiguity, in particular, on the expression of this phenomenon among somatic phraseological units in the Uzbek language. Somatic phraseology, that is, words related to the name of parts of the human body, describes the phenomenon of ambiguity.In world and Uzbek linguistics, there are some comments on the work carried out in this direction. Numerous phraseological expressions of the somatic component in the Uzbek language were used to explain the causes of this phenomenon, as well as the methodological branch.The article analyzes ambiguous phrases with the components “ko’z”, “qo’l”, “og’iz” in the Uzbek language. The results of the analysis are confirmed by examples from fiction.The homonymy of somatic phrases allowed them to be studied by analogy, relying on the material of linguistic dictionaries of the Uzbek language, which, in turn, helped to better understand the semantic and grammatical nature of phraseological meanings. The study of polysemantic meanings in each of them on the basis of distributed analysis methods has proved that the secondary meaning, separated from the leading meaning, has the right to exist in the language as an independent lexical unit.